A taxonomic contribution to the genus Brachythele Ausserer, 1871 (Araneae, Nemesiidae) with a description of a new species from Rhodope Mountains, Bulgaria - Dimitrov, Dragomir; Zonstein, Sergei (Zootaxa, 2022)
We describe Brachythele rhodopensis sp. n. based on the holotype male from the eastern Rhodope Mountains, Bulgaria. The new species is compared with its closest congeners. The diagnosis of B. langourovi Lazarov, 2005 is updated, and the species is reported from the North Macedonia for the first time. New photographs of B. langourovi and illustrations of B. bentzieni Zonstein, 2007 are provided. The male of B. media Kulczyński, 1987 is re-diagnosed and re-described.